Closure of buccosinusal communication with bichat ball: case report (Research, Society and Development, 2020)
Buccosinusal communication occurs after extraction of upper molars due to its anatomical proximity to the maxillary sinus, characterized by the access between the oral cavity and the maxillary sinus due to the defect in bone and soft tissue. The objective was to present a case report of closure of sinus buccal communication with bichat ball. Male patient, 54 years old, attended the Solon Galvão Clinic (Universidade Potiguar - UnP, Natal-RN, Brazil) presenting a sinus buccal communication on the right side of the maxilla resulting from an extraction of the element 17. A maxilla cone bean computed tomography was requested, where it was proven that during the extraction of the element 17, the anterior wall of the maxillary sinus was also removed, causing communication. The maxillary sinus was cleaned, removing inflammatory cysts from inside the cavity. Then, there was exposure and mobilization of the bichat ball, followed by suturing it around the lesion in the mucosa and suture of the mucosa over the bichat ball, using absorbable thread. It is concluded that it is a safe technique, easy to perform, benefiting a satisfactory result for the patient.